Molybdenum and Phosphorous Roles in Biological Nitrogen Fixation Using Rhizobium and Azospirillum in Soybean (Glycine max L.) - Abdul Jabbar, Bassam Kanaan (2011)
Bacterial inoculation for legumes is one of the most important ways in the agricultural sector in improving yield quality and quantity of harvest. The role of Rhizobium is very important to produce better nodulation, nitrogen fixation, growth and higher yield. Azospirillum inoculated as a plant growth promoter gives positive effects in improving root development and the subsequent increase in the rate of water and mineral uptake. Molybdenum in plants is required for efficiency of the nitrogenase enzyme that is required by the nitrogen fixing bacteria whilst phosphorus is the second most limiting nutrient, after nitrogen, required for plant growth. A study was carried out to determine the role and interaction of inoculants, phosphorus and molybdenum in soybean under a drip irrigation system. A series of experiments were conducted in laboratory and glass house conditions with the following objectives; 1- To study the effect of molybdenum on the growth and survival of Bradyrhizobium and Azospirillum under laboratory conditions. 2- To study the effect of phosphorus and bacterial inoculation on the growth and yield of soybean under saline water irrigation. 3- To determine the effect of molybdenum, Bradyrhizobium and Azospirillum on the growth and yield of soybean under drip irrigation system. 4- To study the effect of molybdenum and co- inoculation on the growth and yield of soybean under drip irrigation system. Results from the experiments indicated that coinoculation with Rhizobium and Azospirillum together with molybdenum stimulated total dry matter accumulation and root growth, stimulated uptake and higher concentration of N, P and K compared with inoculation by Rhizobium or Azospirillum alone. In the first experiment two Bradyrhizobium strains UPMR020 and UPMR047 and Iraqi isolate BK1 isolated from the roots of cowpea were used to select the best strain for the glass house conditions. Results showed that UPMR020 gave the best number of nodules, weight of nodules and plant dry weight compared to UPMR047 and isolate BK1, with a significant increase at (P≤0.01). In the second experiment the UPMR020 and UPMR047 were examined to reveal the ability of strains to survive in soil during six periods of incubation. The UPMR020 with 1 kg of Mo/ha showed a higher number of bacteria during five weeks of incubation compared with other treatments. Two Azospirillum species, A.brasilense isolated from roots of corn and A.irakense isolated from root of rice in Iraq were used. Azospirillum.brasilense with 1kg of Mo/ha gave a significant (P≤0.01) numbers of bacteria compared with A.irakense. In fourth experiment different levels of phosphorus (0, 40, 80 and 120 kg of P/ha) with strain UPMR020 was studied together with irrigation using saline water (3.5 dS/m). The results showed an increase in all plant parameters under bacterial inoculation by UPMR020 and 120 kg of P/ha under in spite of irrigation by saline water. From the above we can conclude that UPMR020 and UPMR047 was the best and most effective inoculants; both strains were used in subsequent experiments and it was found out that UPMR020 was better than UPMR047 in growth and survival in soil under laboratory conditions, and highest number of bacteria was under combination of 1 kg of Mo/ha and UPMR020. A.brasilense was the best and very effective inoculant compared with A.irakense in which A.brasilense gave highest number of bacteria under all treatments except interaction with 10 kg of Mo/ha. The phosphorus level at 120 kg of P/ha was the best treatment in increasing all plant parameters during the experiment especially when UPMR020 was added, and 3.5 dS/m saline water was suitable for soybean plants as alternative way of irrigation. One kg of Mo/ha with bacterial inoculation (Rhizobium or Azospirillum) gave highest plant yield and other plant parameters compared with other treatments, while 10 kg of Mo/ha decreased plant parameters with or without bacterial inoculation. Co- inoculation by Rhizobium and Azospirillum with 1 kg of Mo/ha gave highest plant growth parameters compared with other treatments followed by 1.5 kg of Mo/ha. Drip irrigation system proved its efficiency as a very important way in irrigated soybean plants and give better results. Generally co- inoculation by both bacterial strains effectively increased all plant parameters followed by Rhizobium inoculation alone then Azospirillum alone.